1997
DOI: 10.1002/(sici)1097-4652(199704)171:1<20::aid-jcp3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Differential decrease in Connexin 32 expression in ischemic and nonischemic regions of rat liver during ischemia/reperfusion

Abstract: The effect of a localized hepatic injury, regional ischemia/reperfusion, on the expression of connexin 32 (Cx32) was studied. Cx32 is the component of the major hepatic gap junction. Two regions of the injured liver were analyzed: the area directly affected by the ischemic insult (ischemic liver), and the remainder of the organ (nonischemic liver). In the ischemic liver, there were simultaneous reductions in Cx32 mRNA steady-state levels and the encoding polypeptide from the plasma membrane within 1 h of reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Identical changes were seen in concentration of calcium, which is known to move intercellularly through gap junctions [66]. In a similar experimental model, it was found that the reductions in Cx32 mRNA and protein amounts occur at different time points and are driven by different posttranscriptional and posttranslational mechanisms in ischemic and non-ischemic liver areas during reperfusion [67]. In addition to a pronounced inflammatory response, a major factor that contributes to ischemia and reperfusion injury includes the generation of oxygen-derived free radicals [62][63][64].…”
Section: Gap Junctions In Liver Ischemia and Reperfusion Injurymentioning
confidence: 88%
“…Identical changes were seen in concentration of calcium, which is known to move intercellularly through gap junctions [66]. In a similar experimental model, it was found that the reductions in Cx32 mRNA and protein amounts occur at different time points and are driven by different posttranscriptional and posttranslational mechanisms in ischemic and non-ischemic liver areas during reperfusion [67]. In addition to a pronounced inflammatory response, a major factor that contributes to ischemia and reperfusion injury includes the generation of oxygen-derived free radicals [62][63][64].…”
Section: Gap Junctions In Liver Ischemia and Reperfusion Injurymentioning
confidence: 88%
“…Cx32 and Cx26, two parenchymal cells Cxs, are reduced in acute liver inflammation induced by LPS (5,(23)(24)(25)(26), hepatic ischemia/ reperfusion (25), and cholestasis caused by common bile duct ligation (5,27). Under these conditions the expression of Cx43 by KCs, non-parenchymal cells, is enhanced to clear/repair the damage.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Cx32 has been reported to be posttranscriptionally downregulated in rat liver because of a decreased stability of Cx32 mRNA (Gingalewski et al 1996). More recently, Gingalewski and De Maio (1997) have shown that, in addition to the decreased level of Cx32 mRNA, the level of Cx32 protein is decreased in ischemic rat liver.…”
Section: Discussionmentioning
confidence: 99%